Combination of Subcision, Microneedling, and Platelet-Rich Plasma Therapy in Patient with Grade Four Atrophic Acne Scars - Jesryn Dhillon; Khairina Nasution; Nelva Karmila Jusuf (GLOBAL HEALTH SCIENCE GROUP, 2025)
Atrophic acne scars affect up to 75% of patients with a history of acne and are often associated with significant psychosocial distress. These scars are classified into three main types: ice pick, rolling, and boxcar. A multimodal therapeutic approach is often required for effective management, particularly in severe cases. This report presents a case of a 40-year-old married woman with a 10-year history of inflammatory acne lesions that progressed into grade 4 atrophic scars. The acne was suspected to be triggered by injectable contraceptive use, which contains progestins with androgenic activity. The patient frequently picked at her acne, leading to deep scarring predominantly on both cheeks. Based on clinical evaluation, dermoscopy, and skin analyzer assessment, the patient underwent a series of treatments combining subcision, microneedling, and platelet-rich plasma (PRP) therapy. Following treatment, the Self-Assessment of Clinical Acne-Related Scars (SCARS) score improved from 22 to 14, while the Facial Acne Scar Quality of Life (FASQoL) score improved from 32 to 16. This case highlights the effectiveness of a combination approach in remodeling scar tissue and improving quality of life in patients with severe atrophic acne scars. A tailored, comprehensive treatment plan is essential for optimal outcomes.